2019
DOI: 10.1177/1040638719891972
|View full text |Cite
|
Sign up to set email alerts
|

Health assessment of juvenile green turtles in southern São Paulo State, Brazil: a hematologic approach

Abstract: We assessed the health status and hematologic and blood chemistry values of 48 juvenile green turtles ( Chelonia mydas) on the southeastern coast of Brazil (25°S 48°W). We investigated the impact of size and weight, nutritional condition, and presence of epibionts and fibropapilloma tumors. Nutritional status was good for 39 animals; these animals had higher serum albumin, cholesterol, and phosphorus concentrations than 9 animals with a fair nutritional score. Reference values for hematology and biochemistry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
4
1
2
Order By: Relevance
“…In general, the levels of most parameters analyzed in this work are like those found for juveniles of the same species in Brazil (Table 1). However, the average concentration of glucose (winter), total proteins (winter) and total cholesterol are below the mean values found by Santos et al (2015) and Mello and Alvarez (2019). Nevertheless, they are between the range of quantified values.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In general, the levels of most parameters analyzed in this work are like those found for juveniles of the same species in Brazil (Table 1). However, the average concentration of glucose (winter), total proteins (winter) and total cholesterol are below the mean values found by Santos et al (2015) and Mello and Alvarez (2019). Nevertheless, they are between the range of quantified values.…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, results from this study were compared with juvenile green sea turtles from Brazil to confirm that the levels observed were within normal ranges. Only two studies (Santos et al, 2015;Mello and Alvarez, 2019) that analyzed the same parameters were found, one of them also sampled in São Paulo state and the other in Espírito Santo state.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency of Shh (i.e., haploinsufficiency) could interact with other genetic and/or epigenetic factors, leading to holoprosencephaly [59], producing aberrant phenotypes with varying degrees of severity. Interestingly, lower blood cholesterol levels have been reported for green turtles with fibropapilloma (as well as with other pathologies) compared to healthy turtles [60][61][62]. Blood cholesterol has been recently proposed as a biomarker of fibropapillomatosis in green turtles, since cholesterol values are significantly lower when the pathology is more severe [63].…”
Section: Forebrain and Midline Facial Structuresmentioning
confidence: 99%
“…Estudios recientes realizados en los A° Tubichamini, El Gato y Carnaval revelaron diferencias significativas en diversos indicadores de calidad del ambiente a favor del primero respecto de los segundos. El A° Tubichamini presentó mejores parámetros fisicoquímicos e índices bióticos, una mayor diversidad y riqueza de especies plactónicas y bentónicas (macroinvertebrados), tramas tróficas más complejas y presencia de especies sensibles a la contaminación (Alvarez et al 2020.…”
Section: Arroyo Tubichaminiunclassified
“…En las últimas décadas se han realizado diversos estudios en poblaciones naturales de tortugas terrestres, dulceacuícolas y marinas de distintas regiones del planeta que emplean variables hematológicas como indicadores de su estado sanitario, y para inferir su relación con factores ambientales en ecosistemas impactados (Christopher et al 1999, Hidalgo-Vila et al 2007, Chaffin et al 2008, Perpiñán et al 2008, Harris et al 2011, Komoroske et al 2011, Omonona et al 2011, Kimble y Williams 2012, Sheelings y Rafferty 2012, Andreani et al 2014, Lewbart et al 2014, de Mello y Alvarez 2020. La bibliografía de esta temática en tortugas dulceacuícolas sudamericanas está basada casi en su totalidad en poblaciones de Brasil (Zago et al 2010b, Oliveira-Junior et al 2008, Ferronato et al 2009, Rossini et al 2012, Stein et al 2015.…”
Section: Introductionunclassified